The effect of the stiffener pitch on the stress-strain state of the crane beam elements - V. S. Markeev; V. V. Zverev; I. A. Zajcev (Vestnik MGSU)
Introduction. A study of the stress-strain state of split crane beams was carried out, the features of loading from the crane rollers and the effect on the stress-strain state of crane beam elements in terms of formation of fatigue cracks in the upper compressed zone of the wall were highlighted. The main objective of the study is to search for the features of the crane beam construction of cranes with heavy operation mode, to search for methods of modernization of design features in order to prevent/minimize the development of fatigue cracks.Materials and methods. The research is based on long-term experience in the operation of crane beams of heavy and especially heavy operating modes of cranes, data from conclusions based on the results of surveys of building structures, conclusions on industrial safety of hazardous production facilities, scientific publications. Based on the design schemes of existing and actually operated crane beams of the metallurgical enterprise, a computational model of the structure under study was developed in the computational complex of strength analysis of structures by the method of finite element analysis.Results. The stress-strain state of crane beam structures of cranes with heavy and especially heavy operating modes is analyzed, the influence of the position of the crane roller on the condition of various parts of the crane beam structure: walls, belts and ribs is studied. The regularity in the work of structural elements is derived when the frequency of the transverse ribs of crane beams changes. Assumptions are made to solve the strength problem of the formation of unacceptable fatigue cracks in the upper compressed zone of the crane beam wall.Conclusions. Based on the results of numerical analysis of the stress-strain state of the crane beam construction model, data are presented indicating the previously unknown peculiarities of crane beams operation. A hypothesis is given for solving the strength problem of the formation of unacceptable fatigue cracks in the upper compressed zone of the crane beam wall.